Influência de níveis de adubação potássica via fertirrigação no desenvolvimento e na qualidade de frutos do mamoeiro em Neossolo Quartzarênico - Anjos, David Correia dos (2011)
This work had objective to analyze the effect of levels of potassium fertilizer, applied by fertigation, development, productivity and fruit quality of papaya Formosa, Cv. 'No . Tainung. 1', at conditions of Russas - CE. The experiment was conducted following a entirely randonmized design consisting of four doses of K2O (36, 72, 108 and 144 g, corresponding to 60, 120, 180 and 240 g of KCl plant month-1), to apply in irrigation water surface drip in Quartzipsament. Was measured at 150, 210 and 250 days after transplant, the stem diameter and plant height, and 8 months after transplant was evaluated the effect of treatments on the physicochemical characteristics of the fruit. At 720 days was evaluated the effect of treatments on soil chemical characteristics, assessment of the content N, P and K at the foliar and petiole a of the papaya, fruit count per plant, weight per fruit and was estimated productivity of the area. The application of K doses on soil chemical properties significantly influence the levels of Ca, Na, N, P and K, the Mg content in soil did not follow the same behavior. The pH, CE and M.O content in soil had an increase in their values with increasing dose of application of K. The characteristics of stem diameter and plant height measured in papaya plants in the three periods peaked when it was used the dose of KCl 180 g plant-1 month-1, from that plant development was injured by excessive K applied. The higher number of fruits per plant, average fruit weight and yield were obtained with a dose of 240 g of KCl plan month-1. The doses of potassium applied through fertigation had a significant influence on the concentration of N and K in the petiole and the N, P and K in the leaves of the papaya. The concentration of P was not affected by the application of doses of K in the soil. The treatments did not exert significantly different effects on the parameters: fruit weight, peel weight, weight and pulp firmness, but the time of ripening, soluble solid, pH and acidity of the pulp showed significant differences with different doses of K applied through fertigation. The levels of nutrients: nitrogen, phosphorus, potassium and sodium in fruits of papaya showed significant differences between the application of doses of K.